Development plan for the library of the Isabela School for the Deaf - Pascual, Charlito C. Jr.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study was conducted to help the deaf students of the Isabela School for the Deaf, one of the major Deaf schools in the region, in utilizing the library.
Qualitative method of data collection was carried out. A total of 22 respondents forming 4 sets of group discussion from four different institution including the Isabela School for the Deaf were invited to participate in a focus group discussion. Interview with the librarian, staff and administrators were done separately. Statements from the focus group discussions are then sorted out using thematic analysis providing data for SWOT analysis.
Data gathered shows that the deaf students do not have major differences with the hearing relative to their library usage and needs. What they struggle the most at is interaction with the librarian, the resources and the books. One major factor affecting the deaf students is having a different language.
Recommendation were given such as: (a) hiring a licensed librarian that knows sign language and has SPED training; (b) acquire additional books related to language such as dictionaries; (c) acquire additional resources for the Deaf to promote awareness of Deaf culture; (d) acquire easy- to-read books and picture books to encourage reading; (e) acquire updated materials for school; (f) follow the development plan created for the Isabela School for the Deaf.
Thesis (Bachelor of Library and Information Science)
Keywords: Isabela School for the Deaf; Special libraries -- Collection development